Synthesis of New 3-Substituted Quinazolin-4"3H"-one Compounds Via Linking of some Five-MemberedRing Heterocyclic Moieties with Quinazolin-4"3H"-one Nucleus - العراقي، محمد أحمد; سعد الدين، رند أرشد (جامعة الموصل - كلية التربية, 2021)
In this research new compounds containing quinazolin-4 (3H)- one nucleus linked to heterocyclic moieties were synthesized using ethyl (4'-oxoquinazolin-3'-yl) acetate (2) as a synthon. This compound was synthesized via 4-quinazolinone's (1) reaction with ethyl chloroacetate in the existence of K2CO3 as a base and acetone as a solvent. The ethyl α-(4'-oxoquinazolin-3'-yl) acetate (2) was converted to the corresponding hydrazide through its reaction with hydrazine hydrate (85%). Compound (3) was reacted with two of acyl chlorides to synthesize the diacyl hydrazine compounds (4,5). The compound (5) was cyclized to the corresponding 1,3,4- oxadiazole (6) in presence of phosphorous oxychloride. The formyl derivative (7) of the hydrazide (3) was synthesized via its reaction with formic acid and consequently cyclized by phosphorous oxychloride to the corresponding 1,3,4- oxadiazole (8). The hydrazide (3) was also converted to the thiosemicarbazide derivative (9) by its reaction with ammonium thiocyanate under acidic conditions. Whereas other substituted thiosemicarbazide derivatives (10- 12) were synthesized by the reaction of hydrazide (3) with organic isothiocyanate compounds. The resultant compounds (11, 12) were cyclized under basic conditions (4% sodium hydroxide solution) to give 1,3,4- triazole-2- thiole derivatives (13,14), whereas the cyclization of compounds (10- 12) was performed under the acidic medium (conc. H2SO4) to give 2-substituted amino-1,3,4-thiadiazoles (15- 17). On the other side, the hydrazide's (3) reaction with isocyanate compounds affords the semicarbazide compounds (18, 19). These compounds were cyclized under the basic condition to afford 1,3,4- triazol-2-ol compounds (20, 21). The structures of the synthesized compounds were corroborated depending on the physical and spectral data.
يتضمن البحث تحضير مركبات جديدة تحتوي على نواة الكوينازولين -4 (3H) -أون مرتبطة بمجاميع حلقية غير متجانسة باستخدام α- (4- اوكسوكوينازولين - 3 يل )خلات الأثيل مادة أولية (2). حضر هذا المركب عبر تفاعل الكوينازولين -4 (3H) -أون (1) مع كلورو خلات الأثيل بوجود كاربونات البوتاسيوم قاعدة والاسيتون مذيبا. حول مركب الـ α- (4- اوكسوكوينازولين- 3-يل)خلات الأثيل إلى الهيدرازيد المقابل (3) من خلال تفاعله مع الهيدرازين المائي (85%)، استخدم الهيدرازيد (3) مادة أولية لتحضير مجموعة جديدة من المركبات المتضمنة نواة الكوينازولين -4(3H) -أون المرتبطة بمجاميع حلقية غير متجانسة. أدخل الهيدرازيد (3) تفاعلا مع مركبي كلوريد الأسيل لتحضير مركبي الثنائي أسيل هيدرازين (4.5)، ومن ثم تم حولقة المركب (5) بوجود أوكسي كلوريد الفسفور إلى مركب الـ 4.3.1 -اوكسادايازول (6)، كما استخدم الهيدرازيد (3) لتحضير مشتق الفورميل هيدرازيد (7) الذي يتحولق بوجود أوكسي كلوريد الفسفور إلى الـــ 4.3.1 -أوكسادايازول (8). كذلك حول الهيرازيد (3) إلى مركب الثايوسميكاربازيد (9) بتفاعله مع ثايوسيانات الأمونيوم تحت ظروف حامضية. بينما حضرت مشتقات الثايوسميكاربازيد (12 -10) بتفاعل الهيدرازيد (3) مع الثايوسيانات العضوية. تم حولقة المركبين (11, 12) تحت ظروف قاعدية (4% من محلول هيدروكسيد الصوديوم) ليعطيان مركبي الـ 4.3.1 -ترايازول -2- ثايول (13, 14) بينما تتحولق المركبات (10 -12) تحت الظروف الحامضية (حامض الكبريتيك المركز) لتعطي مركبات 2- امينو معوض -4.3.1 -ثايادايازول (15 -17). من ناحية أخرى يتفاعل الهيدرازيد (3) مع الآيزوسيانات العضوية ليعطي مركبات السمي كاربازيد (18 -19) التي تتحولق تحت الظروف القاعدية إلى مركبات الـ 4.3.1 -ترايازول -2- أول (20.21). شخصت تراكيب المركبات المحضرة اعتمادا على البيانات الفيزيائية والطيفية.
Keywords: علم الكيمياء -- المركبات الكيميائية -- معوض كوينازولين -- المجاميع خماسية الحركة -- نواة الكوينازولين